“GUNS AND SHIPS AND SO THE BALANCE SHIFTS”: USING ARTIFACT PATTERNING TO CONTEXTUALIZE A SALVAGED ASSEMBLAGE DATED TO THE BATTLE OF YORKTOWN, 1781 - Schuler, Jillian (East Carolina University, 2023)
Before General Charles Cornwallis surrendered at Yorktown in 1781, he scuttled a portion of his shipping fleet along the Yorktown riverbank to defend the town from a Franco- American amphibious attack. An environment rife with maritime material culture, the river has been subject to formal and informal salvage, including a joint effort in the 1930s by the Mariners' Museum and the National Park Service that produced a significant artifact assemblage with minimal archaeological context. This thesis will attempt to contextualize the 1930s salvaged assemblage of York River through an artifact pattern developed from four case studies: HMS Invincible (1758), HMS Swift (1770), General Carleton (1785), and Betsy (1781). The artifact pattern presents potential archaeological distinctions between British naval and merchant vessels during the second half of the 18th century.
Keywords: American War of Independence; Battle of Yorktown; Maritime Material Culture; Artifact Patterning; 18th Century British Navy; Salvage archaeology--Virginia--York River; United States--History--Revolution, 1775-1783; Underwater archaeology--Virginia--York River; Invincible (Ship : 1744-1758); General Carleton (Ship); Betsy (Ship); Swift (Sloop of war)